Conservation, Regulation, Synteny, and Introns in a Large-scale C. briggsae–C. elegans Genomic Alignment - Kent, W. James; Zahler, Alan M. (Genome Research, 2000)
A new algorithm, WABA, was developed for doing large-scale alignments between genomic DNA of different species. WABA was used to align 8 million bases of Caenorhabditis briggsae genomic DNA against the entire 97-million-base Caenorhabditis elegansgenome. The alignment, including C. briggsae homologs of 154 genetically characterized C. elegans genes and many times this number of largely uncharacterized ORFs, can be browsed and searched on the Web (http://www.cse.ucsc.edu/∼kent/intronerator). The alignment confirms that patterns of conservation can be useful in identifying regulatory regions and rarely expressed coding regions. Conserved regulatory elements can be identified inside coding exons by examining the level of divergence at the wobble position of codons. The alignment reveals a bimodal size distribution of syntenic regions. Over 250 introns are present in one species but not the other. The 3′ and 5′ intron splice sites have more similarity to each other in introns unique to one species than in C. elegans introns as a whole, suggesting a possible mechanism for intron removal.